Critical Role of CA1 Nicotinic Receptors on Memory Acquisition Deficit Under Induction of Total Sleep Deprivation and REM Sleep Deprivation - Javadmoosavi, Bibi zahra; Vaezi, Gholamhassan; nasehi, mahammad; Haeri- rouhani, seyed- Ali; Zarrindast, Mohammad-Reza (International Clinical Neuroscience Journal, 2018)
Objective: Sleep disorder or sleep deprivation (SD) is a common issue in today’s society. Numerous evidences show that sleep is essential for proper brain performance and cognitive processes; on the other hand, cognitive functions have a broad range with learning and long-term memory as the most important ones related to attention. Since many studies show that cholinergic system has a significant role in sleep, learning, and memory, this study aims to investigate the impacts of CA1 Cholinergic Nicotinic Receptors on memory acquisition deficit which is stimulated by total sleep deprivation (TSD) and REM sleep deprivation (RSD). Methodology: In this study a water box or a multi-platform apparatus was used in order to induce total sleep deprivation (TSD) or REM sleep deprivation (RSD). In order to investigate interactions of cholinergic system and hippocampus-dependent memory, nicotinic receptor agonist (nicotine) or nicotinic receptor antagonist (mecamylamine) was injected in hippocampal CA1. Results: According to the results of this study, 24 hours TSD or RSD decreased memory acquisition and injection of nicotine (0.0001 or mecamylamine (0.001 in TSD and RSD sham groups didn’t change memory acquisition. However, injection of sub-threshold dose of nicotine (0.0001 and mecamylamine (0.001 could reduce negative effects of SD in both TSD and RSD. Discussion; According to the present study, cholinergic nicotinic receptors are effective in learning and memory improvement.